Something wonderful : Rodgers and Hammerstein's Broadway revolution - Purdum, Todd S. (Henry Holt and Company, 2018)
"Even before they joined forces, Richard Rodgers and Oscar Hammerstein II had written dozens of Broadway shows, but together they pioneered a new art form: the serious musical play. Their songs and dance numbers served to advance the drama and reveal character, a sharp break from the past and the template on which all future musicals would be built. [This is a portrait of that creative partnership]"--Amazon.com.